Geophysical subsurface characterization of a complex geological terrain for groundwater resource development: case study of Iju, Nigeria - Omowumi Ademila; John Olukunle Ademila (Jurnal Geofisika, 2022)
Access to potable water facilitates rapid civilization, health and social stability in different regions of the world. Subsurface exploration involving detailed geological, geophysical; very low frequency electromagnetic (VLF-EM), electrical resistivity method using vertical electrical sounding (VES) techniques and hydrogeological survey was carried out to characterize the subsurface geological and hydrogeological conditions with a view to developing a contemporary groundwater resources scheme. This is to meet the demand for water and improve the lives of the residents in the study area. Groundwater flows from eastern, northeastern and northern directions to the central, northwestern, southeastern, southern and western parts of the area. Conductive zones within the subsurface established by the VLF-EM survey constitute the forty-seven (47) locations further investigated by VES techniques. Three to five geologic layers were identified, while the weathered and fractured bedrock form the aquifer units with depth in the range 3.5 to over 100 m. The fractured aquiferous unit represents the target aquifer due to its characteristic thick sandy geological formation (mean resistivity; 602 ± 140 Ohm-m) being more prolific in groundwater yielding capacity. Bedrock depressions with thick overburden (> 25 m) were identified as viable groundwater potential zones. Hydrogeological maps generated give insight into geological conditions of the aquiferous units. Groundwater potential map of the area categorizes aquiferous zones based on their yield potential. High groundwater yield potential zones of the area can be harnessed for massive groundwater development scheme. Other zones can be of use as the need arises.